Microwave-assisted extraction of polysaccharides from the marshmallow roots: Optimization, purification, structure, and bioactivity - Hashemifesharaki, Reza; Xanthakis, Epameinondas; Altintas, Zeynep; Guo, Yan; Gharibzahedi, Seyed Mohammad Taghi (My University, 2020)
The process optimization and biological characterization of marshmallow root polysaccharides (MRPs) obtained from the microwave-assisted extraction (MAE) were studied. The highest MAE-yield (14.47%) was optimized at 457.32 W and 75 °C for 26 min. The extracted crude polysaccharides were purified using ion-exchange and gel-filtration chromatographies and eluted a single symmetrical narrow peak, showing a homogenous fraction (MRP-P1) with a molecular weight of 4.87 × 104 Da. The surface morphology of polysaccharides and functional groups of MRP-P1 were determined by employing scanning electron microscopy and Fourier-transform infrared spectroscopy, respectively. The major monosaccharide composition of MRPs were the three monomers of rhamnose, galactose, and glucose. The antioxidant, antimicrobial, and antitumor activities were increased in a concentration-dependent manner (1.0-10.0 mg/mL). MRP-P1 exhibited a strong in vitro antiproliferative activity against lung (A549), liver (HepG2), and breast (MCF-7) cancer cells. The anticancer activity of polysaccharides extracted under optimal MAE conditions was highly associated with their antioxidant and antibacterial functions.
Keywords: Althaea officinalis L.; Biological properties; Extraction; FTIR; Functional properties; Microwave; Polysaccharide